2000
DOI: 10.1096/fj.14.10.1318
|View full text |Cite
|
Sign up to set email alerts
|

p12DOC-1, a growth suppressor, associates with DNA polymerase alpha/primase

Abstract: p12(DOC-1) is a growth suppressor identified and isolated from normal keratinocytes. Ectopic expression of p12(DOC-1) in squamous carcinoma cells led to the reversion of in vitro transformation phenotypes including anchorage independence, doubling time, and morphology. Here we report that p12(DOC-1) associates with DNA polymerase alpha/primase (pol-alpha:primase) in vitro and in cells. The pol-alpha:primase binding domain in p12(DOC-1) is mapped to the amino-terminal six amino acid (MSYKPN). The biological eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…CDK2AP1, a novel cell cycle regulator, has been shown to regulate cell cycle by interacting with CDK2 and preventing phosphorylation of pRB, thus rendering pRB active and able to regulate cell cycle [99]. CDK2AP1 has also been shown to interact with DNA polymerase-α/primase and reduce its activity [100]. This interaction affects the initiation, but not elongation step of DNA replication.…”
Section: Genetic Alteration In Preneoplastic Lesionsmentioning
confidence: 99%
“…CDK2AP1, a novel cell cycle regulator, has been shown to regulate cell cycle by interacting with CDK2 and preventing phosphorylation of pRB, thus rendering pRB active and able to regulate cell cycle [99]. CDK2AP1 has also been shown to interact with DNA polymerase-α/primase and reduce its activity [100]. This interaction affects the initiation, but not elongation step of DNA replication.…”
Section: Genetic Alteration In Preneoplastic Lesionsmentioning
confidence: 99%
“…Murine Cdk2ap1 with only three amino acid deviations from the human CDK2AP1 is located at chromosome 5 (12,13). CDK2AP1 has been shown to be an S-phase regulator through two important cellular partners: CDK2 and DNA polymerase-␣/primase (14,15). Murine embryonic stem cells with disrupted expression of Cdk2ap1 showed an increased proliferation and an altered cell cycle profile with a reduced G 2 /M phase along with an increased CDK2 activity (13).…”
mentioning
confidence: 99%
“…Mechanistic studies have demonstrated that p12 CDK2AP1 binds to DNA polymerase α/primase protein, thereby inhibiting DNA replication (6). In addition, p12…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that p12 CDK2AP1 negatively regulates cell growth by sequestering the monomeric non-phosphorylated form of CDK2 and targeting it for proteolysis to reduce the active pool of CDK2 in cells (5). The protein also reduces CDK2-mediated retinoblastoma protein phosphorylation by reversing the activity of TGF-β (6). A previous study has demonstrated that miR-21 downregulates p12 CDK2AP1 to stimulate cell proliferation and invasion (7).…”
Section: Introductionmentioning
confidence: 99%